2014
DOI: 10.1016/j.bone.2014.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Mineralisation of collagen rich soft tissues and osteocyte lacunae in Enpp1 mice

Abstract: Ecto-nucleotide pyrophosphatase/phosphodiesterases (NPPs) hydrolyse nucleotide triphosphates to the corresponding nucleotide monophosphates and the mineralisation inhibitor, pyrophosphate (PPi). This study examined the role of NPP1 in osteocytes, osteoclasts and cortical bone, using a mouse model lacking NPP1 (Enpp1−/−). We used microcomputed tomography (μCT) to investigate how NPP1 deletion affects cortical bone structure; excised humerus bones from 8, 15 and 22-week old mice were scanned at 0.9 μm. Although … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 53 publications
4
48
0
Order By: Relevance
“…From this data, we concluded that Enpp1 deficiency resulted in no changes in osteoclast formation or resorptive activity. We noted that these observations concur with similar findings in Enpp1 null mice …”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…From this data, we concluded that Enpp1 deficiency resulted in no changes in osteoclast formation or resorptive activity. We noted that these observations concur with similar findings in Enpp1 null mice …”
Section: Resultssupporting
confidence: 92%
“…Murine models of Enpp1 deficiency exhibit the essential characteristics of human GACI, including arterial calcifications, neointimal hyperplasia, cardiac dysfunction, and myocardial infarctions . However, in contrast to the rickets present in human ARHR2, the skeletal phenotype present in Enpp1‐deficient mice is reported to be osteopenic/osteoporotic . Osteomalacia, the defining histology of rickets in ARHR2 children, has thus far not been observed in murine models.…”
Section: Introductionmentioning
confidence: 99%
“…This PP i can then act locally to regulate the level of calcification. Consistent with this, NPP1 knockout mice ( Enpp1 −/− ) display extensive ectopic calcification in a variety of soft tissues including the aorta, kidney, cartilage, ear pinna, and whisker vibrissae (Hajjawi et al, ; Johnson et al, ; Mackenzie et al, ). Furthermore, mutations in the gene encoding NPP1 lead to the recessive condition Generalised Arterial Calcification of Infancy (GACI) which is characterized by extensive vascular calcification (Rutsch et al, ).…”
Section: Introductionmentioning
confidence: 80%
“…A number of factors could contribute towards the differences between the in vivo and in vitro data. Firstly, Enpp1 −/− mice have a complex phenotype and thus it is possible that alterations in other tissues could indirectly influence bone mass (Mackenzie et al, ); for example, Enpp1 −/− animals have increased levels of serum sclerostin, a key inhibitor of bone formation (Hajjawi et al, ). Secondly, Enpp1 −/− mice display an unusual walking gate (Sali et al, ), mineralisation of the joints and muscle damage (Mackenzie et al, ), which combined are likely to affect the mechanical loading of bones.…”
Section: Discussionmentioning
confidence: 99%